Antinociceptive, anti-inflammatory and antipyretic effects of Solanum nigrum aqueous extract in animal models - Zakaria, Zainul Amiruddin; Sulaiman, Mohd Roslan; Morsid, Nur Atiqah; Aris, Anwariah; Zainal, Hairani; Mohd Pojan, Nur Hidayu; Kumar, Gopalan Hanan (Prous Science, 2009)
The present study was carried out to evaluate the antinociceptive, anti-inflammatory and antipyretic effects of the aqueous extract of Solanum nigrum leaves using various animal models. The extract, at concentrations of 10, 50 and 100%, was prepared by soaking (1:20; w/v) air-dried powdered leaves (20 g) in distilled water (dH2O) for 72 h. The extract solutions were administered subcutaneously in mice/rats 30 min prior to the tests. The extract exhibited significant (P < 0.05) antinociceptive activity when assessed using the abdominal constriction, hot plate and formalin tests. The extract also produced significant (P < 0.05) anti-inflammatory and antipyretic activities when assessed using the carrageenan-induced paw edema and brewer's yeast-induced pyrexia tests, respectively. Overall, these activities occurred in a concentration-dependent manner, except for the 50% concentration of the extract, which was not effective in the abdominal constriction test. In conclusion, the present study demonstrated that S. nigrum leaves possessed antinociceptive, anti-inflammatory and antipyretic effects and thus supported traditional claims of its medicinal uses.